Monocytic Cytokines in Autoimmune Polyglandular Syndrome Type 2 Are Modulated by Vitamin D and HLA-DQ - Kraus, Anna U.; Penna-Martinez, Marissa; Shoghi, Firouzeh; Meyer, Gesine; Badenhoop, Klaus (Frontiers in Immunology, 2020)
Context: Autoimmune polyglandular syndrome (APS-2: autoimmune Addison´s disease or type 1 diabetes) is conferred by predisposing HLA molecules, vitamin D deficiency and heritable susceptibility. Organ destruction is accompanied by cytokine alterations. We addressed the monocytic cytokines of two distinct APS-2 cohorts, effects of vitamin D and HLA DQ risk. Methods: APS-2 patients (n=30) and healthy controls (n=30) were genotyped for HLA DQA1/DQB1 and their CD14+ monocytes stimulated with IL1β and/or 1,25(OH)2D3 for 24 h. Immune regulatory molecules (IL-6, IL-10, IL-23A, IL 15, CCL-2, PD-L1), vitamin D pathway gene transcripts (CYP24A1, CYP27B1, VDR) and CD14 were analyzed by enzyme-linked immunosorbent assay and RTqPCR. Results: Pro-inflammatory CCL-2 was higher in APS-2 patients than in controls (p = 0.001), whereas IL-6 showed a trend – (p = 0.1). In vitro treatment with 1,25(OH)2D3 reduced proinflammatory cytokines (IL-6, CCL-2, IL-23A, IL-15) whereas anti-inflammatory cytokines (IL-10 and PD-L1) rose both in APS-type 1 diabetes and APS-Addison´s disease. Patients with adrenal autoimmunity showed a stronger response to vitamin D. Expression of IL 23A and vitamin D pathway genes VDR and CYP27B1 varied by HLA genotype and was lower in healthy individuals with high-risk HLA (p = 0.0025; p= 0.04), while healthy controls with low-risk HLA showed a stronger IL-10 and CD14 expression (p = 0.01; p = 0.03). Conclusion: 1,25(OH)2D3 regulates the monocytic response in APS-2 disorders type 1 diabetes or Addison´s disease. The monocytic cytokine profile of individuals carrying HLA high-risk alleles is proinflammatory, enhances polyglandular autoimmunity and can be targeted by vitamin D.